Associations between environmental glyphosate exposure and glucose homeostasis indices in US general adults: a national population-based cross-sectional study - Xiaobing Feng; Min Wang; Yuji Wang; Ruyi Liang; Chunxiang Yan (Scientific Reports)
Abstract As glyphosate’s application becomes increasingly widespread across the globe, its potential adverse effects on humans have garnered growing concerns. Little evidence has revealed the associations between glyphosate and glucose homeostasis. A total of 2094 individuals were recruited from the NHANES 2013–2018. Urinary glyphosate, alkaline phosphatase (ALP), fasting plasma glucose (FPG), fasting insulin, and glycated hemoglobin A1c (HbA1c) were measured. Homeostatic model assessment of beta-cell function (HOMA2-β), insulin resistance (HOMA2-IR), and insulin sensitivity (HOMA2-IS) were assessed. Generalized linear models and mediation analyses were fitted to estimate the potential associations between glyphosate, glucose homeostasis, and ALP. Urinary glyphosate demonstrated a statistically significant positive association with FPG and HbA1c in a linear positive dose–response manner, while showing a linear negative association with HOMA2-β. Each doubling increase in urinary glyphosate was associated with a 1.13%, 1.50%, and − 2.80% alteration in FPG, HbA1c, and HOMA2-β, respectively. Obesity modified the association between urinary glyphosate and glucose dyshomeostasis with stronger associations in obese individuals. In addition, elevated ALP significantly mediated the associations of urinary glyphosate with FPG and HbA1c, with mediated proportions of 9.91% and 20.23%, respectively. Environmental glyphosate exposure was associated with glucose dyshomeostasis, which was more pronounced in obese individuals and was partly mediated by ALP.